Pediatric graduate students’ and pediatricians’ knowledge and habits on child oral health - Urman, Gabriela (2023)
Objective: To analyze child oral health training background, habits and knowledge in a group of pediatric graduate students and recently graduated pediatricians. Materials and methods: A descriptive study using an anonymous self-administered 18-item survey sent via Google Forms to students and graduates of a master’s program in Pediatrics from Universidad Maimonides in the Autonomous City of Buenos Aires, Argentina. Results: Sixty participants completed the survey: 80 % were women, most of them with no children, who were pursuingone of the three years of a master’s program or had less than two years of clinical experience. Out of the respondents, 78.9 % did not usually record information on oral health in the patients’ medical records, and 72 % failed to establish the prevalence of cavities in relation to other childhood illnesses. Misconceptions were also found regarding cavities etiology. A total of 67.2 % have had no prior oral health training, and those who had had such training stated that it had been insufficient. The self-perception to carry out preventive actions was uneven, and difficulties were identified for the early detection of dental disease. Sixty percent were unable to establish the right amount of toothpaste recommended for a child and felt unprepared to offer advice on the right brushing technique. Likewise, in the sample there were no correctand uniform criteria for the first visit of healthy children to pediatric dentists. Conclusions: As stated by other authors, deficiencies were found in pediatric graduate students’ and recently graduated pediatricians’ training and, therefore, self-perception of topics related to oral health. Despite the difficulties participants identified, they agreed on the key role pediatricians play in oral health prevention and its impact on children’s quality of life.